7 years of Ugnayan ng Pahinungod System the gurong pahinungod program in focus. - University of the Philippines System ([Quezon City] Ugnayan ng Pahinungod System, 2001)
"As the Pahinungod System Office comes to a close on March 31, 2001, we leave the pahinungods - past, present and future - this token of thanksgiving. Likewise, it poses the continuing challenge to the University of the Philippines to harness its comparative advantage in education in the service of the nation."--Preface.
Preface -- Part 1. Linkages and services -- Introduction -- Pahinungod System : 1994-1999 -- The Ugnayan ng Pahinungod support mechanism -- The transition period (1999-2001) -- Pahinungod goes international -- System office & Kaibigan host-seminar workshop -- PNVSCA awardee -- Part 2. The Gurong Pahinungod Program -- Introduction -- The program -- Implementation -- Monitoring and evaluation -- Financial administration -- Achievements -- Challenges -- Info bits -- References -- Annexes -- Part 3. Felicitations and affirmation -- Messages.